Memoria de gestión : 1982-1985 : [al] 4° Congrés : Alacant, 19-20-21 [de] abril [de 1985] / Vicesecretaría General [y] Grupo Parlamentario Socialista de las Cortes Valencianas [del] PSPV-PSOE
Datos tomados de la cub.